An approach to the biological, historical and psychological repercussions of gender verification in top level competitions - Martinez-Patino, M. J.; Mateos-Padorno, C.; Martinez-Vidal, A.; Sanchez Mosquera, A. M.; Garcia Soidan, J. L.; del Pino Diaz Pereira, M.; Tourino-Gonzalez, C. G. (Journal of Human Sport & Exercise, 2010)
Different kinds of disorders of sex development (DSD) have been observed in athletes from different countries along the history of sport. The detection of an abnormal chromosomal pattern or gonadal dysgenesis has been always associated to the gender verification tests which international sports institutions have performed from 1960s and abandoned as systematic practice in 2000. Such methods have been heavily criticized by specialists of different fields such as genetics, endocrinologists and psychologists. The use of a femininity control at the present days to detect possible males who fraudulently pretend to compete in female only events is inconsistent. The possible decision of the International Olympic Committee to establish special centers to manage future DSD cases is also discussed. A major concern on the confidentiality between doctors and patients and the establishment of care protocols for the psychological support of athletes in such delicate situations is needed. This ties altogether with the psychological and social repercussions of the gender verification on the lives of athletes with DSD. When cases of sex ambiguities are detected, issues such as the respect of privacy, the need of specific protocols to follow with flexible and diversified tests considering the particularity of each case as well as the psychological support of the athletes and their family have to be taken into account. Although health tests are needed for both men and women, DSD athletes should not be discriminated for their genetic pattern and they should be allowed to compete as it occurs with other athletes with genetic affections which do not involve the sex and that give them a phenotypical advantage over other athletes.